Pengaruh Model Pembelajaran Contextual Teaching Learning (CTL) terhadap Hasil Belajar Siswa pada Mata Pelajaran IPA di Kelas V UPTD SD Negeri 122353 Pematangsiantar - Nora Melviani Napitupulu; Muktar Panjaitan; Hetdy Sitio (Journal on Education, 2023)
This study aims to improve student learning outcomes in Science Subject Class V UPTD SD Negeri 122353 Pematangsiantar by using the Contextual Teaching and Learning (CTL) Learning Model. Researchers used Pre- Experimental Design (limited number of samples to be studied) using One group pretest and posttest, namely one experimental group measured the dependent variable (posttest) without any comparison group. The sample used in this study were 30 students. The data collection instrument used was a multiple choice question sheet which was given through a pretest and posttest. The data from this study were analyzed using descriptive analysis techniques and inferential analysis techniques. From the results obtained from the t-test, the tcount value is 13.77 and t_table is 2.048, (count)> ttable = 13.77 > 2.040, the difference between the pretest and posttest results is significant and it can be concluded that Ho is rejected and Ha is accepted. , which means that the hypothesis in this study is accepted, namely that there is a positive influence of the Contextual Teaching And Learning (CTL) learning model on student learning outcomes in science lessons in class V UPTD SD Negeri 122353 Pematangsiantar.